Novel variant of dual left anterior descending artery arising from single right coronary artery anomaly presenting with angina inversa - Cingoz, Faruk; Arslan, Gokhan; Iyisoy, Atilla; Bingol, Hakan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
A 55-year-old female without a history of coronary artery disease, hypertensive for the past 17 years, was admitted with resting chest pain. Electrocardiography revealed a negative T-wave in anterior chest leads. Coronary angiography visualised anomalous coronary anatomy, with a common origin of the right coronary artery and the left main coronary artery in the right sinus of Valsalva serving as a common coronary trunk. It should be emphasised that T-wave abnormalities and chest angina may be related to this congenital coronary anomaly.